Variability of Soybean [glycine max (L) Merr] Growth in Relation to Chemical Properties of Ultisol from East Lampung - Taufiq, Abdullah; Wijanarko, Andy (JOURNAL OF TROPICAL SOILS, 2012)
Acidic dry land in Lampung is potential for soybean development area. Low soybean yield in farmer level is one of factor causing its’ low competitiveness. Soil fertility is the main constrain related to low yield of soybean. Objective of the research was to diagnose a cause of poor soybean growth on dry land Ultisol at Sukadana sub District, East Lampung District. Soil and soybean plant samples were collected from farmers’ field at Sukadana ilir village during planting season April – July year 2010. Plant and soil samples were taken when soybean at R1 stage (starting to bloom) using stratified random sampling method. The result showed that variability of soybean growth on Ultisol at Sukadana, East Lampung related to variability of soil pH, exchangeable Al, exchangeable K, Ca, and Mg. The poor soybean growth was due to low soil pH, high exchangeable Al, low exchangeable K, Ca, and Mg.